Mechanics of torque generation in the bacterial flagellar motor - Mandadapu, K; Nirody, J; Berry, R; Oster, G (National Academy of Sciences, 2015)
The bacterial flagellar motor (BFM) is responsible for driving bacterial locomotion and chemotaxis, fundamental processes in pathogenesis and biofilm formation. In the BFM, torque is generated at the interface between transmembrane proteins (stators) and a rotor. It is well established that the passage of ions down a transmembrane gradient through the stator complex provides the energy for torque generation. However, the physics involved in this energy conversion remain poorly understood. Here we propose a mechanically specific model for torque generation in the BFM. In particular, we identify roles for two fundamental forces involved in torque generation: electrostatic and steric. We propose that electrostatic forces serve to position the stator, whereas steric forces comprise the actual “power stroke.” Specifically, we propose that ion-induced conformational changes about a proline “hinge” residue in a stator α-helix are directly responsible for generating the power stroke. Our model predictions fit well with recent experiments on a single-stator motor. The proposed model provides a mechanical explanation for several fundamental properties of the flagellar motor, including torque–speed and speed–ion motive force relationships, backstepping, variation in step sizes, and the effects of key mutations in the stator.